2007
DOI: 10.1037/0012-1649.43.3.576
|View full text |Cite
|
Sign up to set email alerts
|

Sensory modality, temperament, and the development of sustained attention: A vigilance study in children and adults.

Abstract: Applying optimal stimulation theory, the present study explored the development of sustained attention as a dynamic process. It examined the interaction of modality and temperament over time in children and adults. Second-grade children and college-aged adults performed auditory and visual vigilance tasks. Using the Carey temperament questionnaires (S. C. McDevitt & W. B. Carey, 1995), the authors classified participants according to temperament composites of reactivity and task orientation. In a preliminary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…This study used an auditory task that required sustained listening attention, or “vigilance” (Aylward, Brager, & Harper, 2002; Borgaro et al, 2003; Curtindale, Laurie-Rose, Bennett-Murphy, & Hull, 2007; Erickson, Goldinger, & LaPointe, 1996; Seli, Cheyne, Barton, & Smilek, 2011). An auditory vigilance task was selected because of its ecological validity, as sustained auditory attention is often concurrent with real-world actions (Hubal, Reyes, & Newlin, 2009; Pang et al, 2005; Yantz, Johnson-Greene, Higginson, & Emmerson, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…This study used an auditory task that required sustained listening attention, or “vigilance” (Aylward, Brager, & Harper, 2002; Borgaro et al, 2003; Curtindale, Laurie-Rose, Bennett-Murphy, & Hull, 2007; Erickson, Goldinger, & LaPointe, 1996; Seli, Cheyne, Barton, & Smilek, 2011). An auditory vigilance task was selected because of its ecological validity, as sustained auditory attention is often concurrent with real-world actions (Hubal, Reyes, & Newlin, 2009; Pang et al, 2005; Yantz, Johnson-Greene, Higginson, & Emmerson, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…It bears some relation to the approach of Kagan and Snidman (2004) in considering temperament as differences in the reactivity of underlying neural systems, and is related to the category of negative affectivity described by Rothbart and colleagues (Rothbart, Ahadi, Hershey, & Fisher, 2001). A scale to assess infant reactivity was created by calculating the average of the z-scores for the intensity and threshold scores, following the work of Curtindale et al (Curtindale, Laurie-Rose, Bennett-Murphy, & Hull, 2007). The alpha coefficient for the reactivity scale was 0.58, which is similar to that found in previous investigations with older children (Curtindale et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…A scale to assess infant reactivity was created by calculating the average of the z-scores for the intensity and threshold scores, following the work of Curtindale et al (Curtindale, Laurie-Rose, Bennett-Murphy, & Hull, 2007). The alpha coefficient for the reactivity scale was 0.58, which is similar to that found in previous investigations with older children (Curtindale et al, 2007). …”
Section: Methodsmentioning
confidence: 99%
“…Although most temperament research has focused on children, temperament remains relevant also in adolescence and adulthood (Thomas & Chess, 1977). Learning and Individual Differences 22 (2012) Temperament traits predict attention (Curtindale, Laurie-Rose, Bennett-Murphy, & Hull, 2007), interests, motivation (Elliot & Thrash, 2002), cognitive strategies (Davis & Carr, 2002), and therefore also working styles (Kristal, 2005). Some studies have shown that associations of temperament and factors related to working styles are moderate or large in magnitude (Davis & Carr, 2002).…”
Section: Introductionmentioning
confidence: 99%